ARTHROPODA TANAH DI PERKEBUNAN KELAPA SAWIT: Perbandingan Populasi Arthropoda Pada Serasah dan Tanah Mineral - Putro Hairutomo Setiko dan Erwinda (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2021)
Agricultural cultivation activities can affect the distribution and population of soil fauna (Arthropods). They are was known as bioindicators of soil health and fertility. The addition of population, the reduction of diversity of certain of species, as well as the migration of a number of fauna can describe the condition of an environment. Based on this, the research was conducted on oil palm plantations that have various plant maintenance management treatments in order to optimize crop production. The research is located at PTPN VIII Cikasungka, Bogor Regency. The process of collecting soil fauna is carried out by sampling the soil, according to a predetermined transect line and putting it into the extractor (Kempson). The sampling time was carried out at the end of the dry season. The results showed that the average population of soil Arthropods was mostly found in the soil (1.050 individu/m2), while in litter the number was less (784 individu/m2). Where Acari and Collembola are the most Arthropods found both in litter and in the soil. Seeing the high population and biodiversity, that is still maintained despite the dry season, it can be said that the management carried out by PTPN VIII Cikasungka has prioritized the sustainability of the ecosystem within in.